Innovative business model of nanocorporation: theoretical prerequisites and experience of implementation in Kazakhstan enterprises - Джилкибаев, Ж.; Мусапиров, Х. (Journal of Economic Research & Business Administration, 2018)
The selected research topic is currently relevant, especially for enterprises in Kazakhstan: in many companies there is a significant gap between the strategic goals and plans and the actual results of current activities. According to the research, on average, companies “generate” only 63% of the financial result that their strategies promise. Not infrequently declared projects in companies remain unrealized, the conceived goals are unattainable. This is especially true for the set goals in interdisciplinary areas – reducing costs, ensuring quality, rhythm and discipline of supply, reducing the time of operations, etc. Effectively solve emerging problems and achieve goals help the thinking of successful managers (design thinking, process approach), the application of the proposed business model of the nanocorporation, as well as adequate managerial innovations. The model of a nanocorporation involves a set of independent, specialized supply firms with a small coordinating core link at the head (network enterprise). In a nanocorporation, business processes are directed not so much to the organization, but as to integration with suppliers (networking). The core company develops its core competence and specializes in corporate governance, planning, and marketing. Expanding partner business network provides fast business growth, minimization of costs, high mobility.